Land Conflict, Migration, and Citizenship in West Africa : Complex Diversity and Recurring Challenges - Maze, Kerry (World Bank, Washington, DC, 2015)
Land and property rights, migration, and citizenship are complex issues that cut across all social, economic, and political spheres of West Africa. This paper provides an overarching scoping of the most pressing contemporary issues related to land, migration, and citizenship, including how they intersect in various contexts and locations in West Africa. The way issues are analytically framed captures structural challenges and sets them against the regional and global meta-trends of which policy makers and practitioners should be aware for conflict-sensitive planning. The paper points to some of the effective practices in managing and mitigating these issues and also raises several questions on areas for future research. Part one lays out the migratory context in West Africa. It points to the type, nature, and extent of mobility that characterizes the region. Part two sets out West Africa’s land tenure and management systems, including structural challenges, general management policies, and key issues related to land tenure and migrants. Part three frames the key land and migration meta-trends in the context of fragility. Part four concludes with an overall exploration of the paper’s results and puts forward a series of research questions that are necessary in order to discern the most effective and realistic operational approaches.